To solve this problem it is necessary to apply the equations related to the conservation of momentum.
This definition can be expressed as
[tex]m_1u_1+m_2u_2 = (m_1+m_2)V_f[/tex]
Where
[tex]m_{1,2}[/tex] = Mass of each object
[tex]u_{1,2}[/tex] = Initial Velocity of each object
[tex]V_f[/tex]= Final velocity
Rearranging the equation to find the final velocity we have,
[tex]V_f = \frac{m_1u_1+m_2u_2}{(m_1+m_2)}[/tex]
Our values are given as
[tex]m_1 = 96Kg\\m_2 = 0.9Kg\\u_1 = 6.3m/s\\u_2 = 27.4m/s[/tex]
Replacing we have,
[tex]V_f = \frac{(96)(6.3)+(0.9)(27.4)}{(96+0.9)}[/tex]
[tex]V_f = 6.4959m/s[/tex]
Therefore the final velocity is 6.5m/s